2019
DOI: 10.3390/ma12111863
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Natural Rubber Filled with Foundry Waste Derived Fillers

Abstract: The main aim of this study is to evaluate the possibility of applying foundry dust (FD) derived filler for the preparation of natural rubber (NR) based composites by characterizing the mechanical properties. The as-received FD was processed via a simple and low-cost procedure, including sieving, deironing and milling using a variety of industrial equipment. FD powders before and after silane coupling agent (Si 69) modification were used as fillers for NR. NR composites inserted with different content of modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…It also reflects the dissipation of energy. As can be seen from the Figure 5, the damping ratio λ can be defined with Equation (8) according to Hardin and Drmevich [39]. The damping ratio is an important dynamic parameter of a soil that expresses the hysteresis characteristics of its stress-strain behavior under cyclic loading.…”
Section: Constitutive Relation and Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…It also reflects the dissipation of energy. As can be seen from the Figure 5, the damping ratio λ can be defined with Equation (8) according to Hardin and Drmevich [39]. The damping ratio is an important dynamic parameter of a soil that expresses the hysteresis characteristics of its stress-strain behavior under cyclic loading.…”
Section: Constitutive Relation and Parametersmentioning
confidence: 99%
“…This excessive accumulation threatens both environmental and human health [ 5 , 6 ]. However, the increasing volume of discarded rubber tires has garnered interest in developing new methods for reusing these materials [ 7 , 8 , 9 ], and thus motivated researchers to characterize the general geotechnical properties of sand–rubber mixtures [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was due to the incompatibility between silica and SBR matrix as silica particles are highly polar while the SBR matrix is a non‐polar material. [ 22 ] By comparing the SEM micrographs of the modified composites (Figure 7B–D) with that of the unmodified composite (Figure 7A), it was found that the distribution of silica within the SBR matrix was improved. This was attributed to the surface modification of silica by CAD, which reduced the surface hydrophilicity of silica and thus improved its dispersion within rubber matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the tensile properties of the modified composites was due the surface modification of silica surface by CAD which improved the interfacial adhesion between SBR matrix and silica. [22][23][24] Accordingly, the stress transfer from SBR matrix to silica was improved. [25] Moreover, it was observed from this figure that the tensile properties of modified composites showed an increase with increasing amount of CAD up to 3 g of CAD and decreasing with the use of an excessive amount of CAD, exceeding 3 g, (S6 composite).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The reduction in the tensile strength can be observed in presence coupling agent (TMSPM) which may be due to the agglomeration and the increased Cu-alloy contents. On the other hand the using of coupling agent (TMSPM) with Cu-alloy leads to the formation of a continuous layer between the EPDM matrix and the copper alloy particles [21,22].…”
Section: Mechanical Propertiesmentioning
confidence: 99%